Estudio del Control Quimico de tagosodes orizicolus muir en oryza sativa l. en Chepén – La Libertad - Alvites Leyva, Jimena Diogelina (2017)
The present research work entitled "Study of the chemical control of Tagosodes orizicolus Muir in Oryza sativa L. in Chepén - La Libertad" was carried out in the fields of the farmers who sow as main rice crop, located in the populated center of Talambo , Region La Libertad. The objective was to study and describe the use of insecticides in the control of Tagosodes orizicolus Muir in Oryza sativa L. in Chepén. The parameters evaluated were: insecticides used, frequency of application, application rates, number of applications, mixtures, chemical control costs, production costs, yield, among others, these data were obtained through the application of surveys. It is concluded that the farmers of Chepén, each season more frequently use the active ingredients like Thiamethoxam, Alfacipermetrin, Thiamethoxam + Lambdacyhalotrin and Imidacloprid, in addition that increase the number of applications of insecticides, increase the doses of application, increase the costs of control and production costs. It is also concluded that each year yields of rice cultivation decrease because of the little success of controlling the Tagosodes orizicolus Muir.